Enhancing Elementary Students’ Mathematical Creative Thinking in Fraction Learning through Canva-Assisted Digital Storytelling - Erni Nurjanah (Program Studi Pendidikan Matematika, Universitas Majalengka, 2026)
Creative thinking has become an essential competency in contemporary mathematics education, particularly in helping students interpret and solve non-routine problems. However, fraction learning at the elementary level is often dominated by procedural instruction, which limits opportunities for students to develop creative mathematical reasoning. This study investigates the effectiveness of Canva-assisted digital storytelling in enhancing elementary students’ mathematical creative thinking in fraction learning. A quasi-experimental design employing a nonequivalent pretest–posttest control group was implemented with 40 third-grade students at MIS Cirumput, Sukabumi, Indonesia. The experimental group received instruction using Canva-based digital storytelling, while the control group received conventional mathematics instruction. Mathematical creative thinking was assessed using essay-based tasks that measured fluency, flexibility, originality, and elaboration. The data were analysed using Analysis of Covariance (ANCOVA) after confirming the assumptions of normality and homogeneity. The results demonstrate a significant effect of the instructional intervention on students’ creative thinking performance (F = 117.9, p < 0.001). Pretest scores were strongly associated with posttest outcomes (η² = 0.558), and the instructional approach contributed substantially to differences between groups (η² = 0.299). Post hoc comparisons indicate that students exposed to Canva-assisted digital storytelling achieved significantly higher posttest scores than those in the control group, with a very large effect size (Cohen’s d = 2.79). These findings suggest that integrating digital storytelling through Canva can support the development of creative mathematical thinking and provide an engaging learning environment for fraction instruction in elementary education